Active Simulation of Grounded Parallel-Type Immittance Functions Employing VDBAs and All Grounded Passive Components - Pratya Mongkolwai; Pitchayanin Moonmuang; Worapong Tangsrirat; T. Suesut (Advances in Science Technology and Engineering Systems Journal, 2023)
This communication proposes a grounded immittance function simulator that, depending on the proper choice of the passive components, can simulate parallel-type impedances of the R-L, R-C, and L-C forms. Only two grounded passive components and two voltage differencing buffered amplifiers (VDBAs) are used to implement the suggested circuit. All three simulated equivalent elements, namely Req, Leq, and Ceq, can be electronically adjusted through the VDBA’s transconductance gain. The impact of the non-ideality of the VDBA device on the developed simulator is examined in detail. The voltage-mode bandpass filter has been implemented using the suggested active LC parallel impedance simulator to show that it performs as predicted. To prove the theory, the proposed circuit is simulated using the PSPICE tool. The findings of the experimental measures are also presented to demonstrate the circuit’s feasibility.
Keywords: Modeling and Simulation Systems; Simulation Techniques and Applications; Real-time simulation and control systems